GM-CSF Monocyte-Derived Cells and Langerhans Cells As Part of the Dendritic Cell Family - Lutz, Manfred B.; Strobl, Herbert; Schuler, Gerold; Romani, Nikolaus (Frontiers in Immunology, 2017)
Dendritic cells (DCs) and macrophages share many characteristics as components of the innate immune system. The criteria to classify the multitude of subsets within the mononuclear phagocyte system are currently phenotype, ontogeny, transcription patterns, epigenetic adaptations and function. More recently, ontogenetic, transcriptional and proteomic research approaches uncovered major developmental differences between Flt3L-dependent conventional DCs (cDCs) as compared with macrophages and monocyte-derived DCs (MoDCs), the latter mainly generated in vitro from murine bone marrow (BM-DCs) or human CD14+ peripheral blood monocytes. Conversely, in vitro GM-CSF-dependent monocyte-derived macrophages largely resemble MoDCs whereas tissue-resident macrophages show a common embryonic origin from yolk sac and fetal liver with Langerhans cells (LCs). The novel ontogenetic findings opened discussions on the terminology of DCs versus macrophages. Here, we bring forward arguments to facilitate definitions of BM-DCs, MoDCs and LCs. We propose a group model of terminology for all DC subsets that attempts to encompass both ontogeny and function.